2019
DOI: 10.1115/1.4040946
|View full text |Cite
|
Sign up to set email alerts
|

Determining Subject-Specific Lower-Limb Muscle Architecture Data for Musculoskeletal Models Using Diffusion Tensor Imaging

Abstract: Accurate individualized muscle architecture data is crucial for generating subject-specific musculoskeletal models to investigate movement and dynamic muscle function. Diffusion tensor magnetic resonance (MR) imaging (DTI) has emerged as a promising method of gathering muscle architecture data in vivo, however its accuracy in estimating parameters such as muscle fiber lengths for creating subject-specific musculoskeletal models has not been tested. Here we provide a validation of the method of using anatomical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 50 publications
2
42
1
Order By: Relevance
“…These data define muscle volume, length, optimal fiber length, fiber pennation angle, PCSA and maximum isometric force. The technique of using DTI and muscle fiber tractography to gather detailed muscle architecture data has been previously described and shown to be valid and repeatable [20, 4256]. In a study into the validity of the technique for gathering muscle architecture specifically for musculoskeletal models, Charles et al, [20] found that DTI can replicate muscle masses, fiber lengths and PCSA within 4%, 1% and 6% of the corresponding variables measured from manual dissections, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These data define muscle volume, length, optimal fiber length, fiber pennation angle, PCSA and maximum isometric force. The technique of using DTI and muscle fiber tractography to gather detailed muscle architecture data has been previously described and shown to be valid and repeatable [20, 4256]. In a study into the validity of the technique for gathering muscle architecture specifically for musculoskeletal models, Charles et al, [20] found that DTI can replicate muscle masses, fiber lengths and PCSA within 4%, 1% and 6% of the corresponding variables measured from manual dissections, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The muscles analyzed were classified into 5 distinct functional groups based on major functions (Table 2), which were based on previous human muscle architecture studies [3]. Muscle fiber length, fiber pennation angle and muscle volumes were estimated from each of these muscles, using a validated framework of magnetic resonance imaging (MRI) and DTI [20]; see below).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations